The development of teacher motivation model for medical universities in Guangxi Province, China - Quan, Yi; Siththada, Thada (Edelweiss Applied Science and Technology, 2024)
Teacher motivation plays a pivotal role in advancing medical education in Guangxi Province, where high-quality education depends on motivated and competent educators. This study assessed the current state of faculty motivation in medical univrsities across the region and proposed a development model tailored to their specific needs. A mixed-methods approach was adopted, combining a cross-sectional survey of 326 faculty members and 74 administrators with semi-structured interviews with key stakeholders. Exploratory factor analysis (EFA) of the survey data revealed five key determinants of faculty motivation: job satisfaction, professional identity, subjective well-being, job burnout, and faculty self-efficacy. Based on these findings and insights from expert interviews, a faculty motivation development model was constructed, alongside practical strategies to enhance motivation. These strategies include fostering a supportive work environment, promoting professional growth, and mitigating burnout. The proposed model offers a robust theoretical framework and actionable recommendations for improving faculty engagement, thereby supporting the advancement of medical education in Guangxi Province and providing a foundation for future research.